Using self-reflection to support higher education teaching - Myllykoski-Laine, Siru; Parpala, Anna; Hailikari, Telle; Postareff, Liisa (Taylor & Francis, 2025)
Seeking ways to support the work of higher education teachers is important. One of the tools that can be used to support teachers’ work is the promotion of reflection. Thus, the current study aimed to explore higher education teachers support opportunities provided by self-reflection. In the study, Finnish higher education teacher educators (N = 20) reflected their teaching by using a research-based self-reflection tool HowUTeach, which consists of items measuring teaching processes and well-being. The teachers responded to the items and then received feedback based on their responses. The teachers then participated in group interviews, which form the data for the present study. Thematic analysis of the interviews focused on teachers’ experiences of the self-reflection and aimed to identify support opportunities the self-reflection and feedback may offer for teachers. Based on the findings, the teachers (1) experienced an enhancement and enrichment of self-reflection, (2) were expecting a more situation-specific approach to self-reflection, and (3) noted support opportunities through the deepening of reflection during collegial interaction. The study highlights that in order to support higher education teachers by promoting self-reflection, it is also crucial to provide teachers with opportunities for dialogical reflection.